The Effect of Leadership on Civil Servant Performance at the Regional Civil Service and Human Resources Development Agency (BKPSDM) of Tojo Una-Una Regency - Siti Rahayu Nibi; Andi Indriani Ibrahim; Wisra Mattalata; Lindanur Sipatu; Rosida P. Adam (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of leadership on civil servant performance at the Regional Civil Service and Human Resources Development Agency of Tojo Una-Una Regency. A quantitative causal-associative design was applied to all 64 employees using total sampling. Primary data were collected through a five-point Likert questionnaire and analyzed using validity, reliability, classical assumption, and simple linear regression tests. Leadership has a positive and significant effect on performance (β = 0.748; t = 8.495; p < 0.001), explaining 53.8% of its variation. Effective leadership is therefore important for strengthening employee performance and public service. Keywords: Leadership; Civil Servant Performance; Public Sector